AN ANALYSIS OF INDIVIDUAL BEHAVIOR IN JANE AUSTEN’S SENSE AND SENSIBILITY: A SOCIAL PSYCOLOGICAL PERSPECTIVE - Larasati, Indah (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
Individual behavior is an outcome reaction of a person to a social engagement or how they perceive themselves in a situation. In Jane Austen’s novel Sense and Sensibility (1811) Elinor and Marianne Dashwood’s behavior is the polar opposite of each other at a certain situation. This study discusses Elinor and Marianne’s behavior during the social events when they are facing situations that occurs. This study aims to observe the cause for the characters behaviors based on the Attribution theory by Harold Kelley. The method used in this study is descriptive qualitative method. The data sources for this study are primary data and secondary data. The primary data is the novel itself and the secondary data sources are from online journals and websites. The result of this study draws conclusion that the reason for the characters behavior shows that they are attributed to external and internal factors.